Photoshop CS4 top 100 simplified tips & tricks - Kent, Lynette (Wiley Pub., 2009)
"Packed with 100 cool and useful tips and tricks, this visual tutorial investigates the bells and whistles that come with the new CS4 release"--Resource description page.
Print version record
Keywords: Adobe Photoshop; Photography -- Digital techniques; Photographie numérique; Photography; Digital techniques